Метод формування інформаційного портрета користувача в мережі інтернет - Говорущенко, Т. О.; Медзатий, Д. М.; Семенюк, В. С.; Hovorushchenko, Tetiana; Medzatyi, Dmytro; Semenyuk, Victor (Видавництво Львівської політехніки, 2018)
Розроблено метод формування інформаційного портрета користувача в мережі інтернет, який дає можливість визначити характеристики, що формують інформаційний портрет користувача, орієнтований на вдосконалення таргетингу інформації або на формування іміджу веб-особистості у мережі інтернет.

The research is devoted to the development of the method for the formation of the user's information portrait on the Internet. The developed method provides the determination of the characteristics, which form the user's information portrait, that is aimed at perfecting the targeting of information or at the formation of the image of the web personality on the Internet.
Method for the formation of the user's information portrait on the internet
Keywords: ідентифікація (відстежування; трекінг; фінгерпринтинг) користувача в мережі інтернет; інформаційний портрет користувача; веб-особистість; таргетинг інформації; identification (tracking; fingerprinting) of the user on the Internet; user's information portrait; web personality; targeting of information; 004.77